ESL Teachers' Experiences with Distributed Leadership during School Improvement Initiatives - Khalil Ahmad,; Rabia Gul,; Arif Khan, (Al-Qanṭara, 2023)
This qualitative study delves into the nuanced experiences of ESL school teachers in Peshawar, Pakistan, as they engage in distributed leadership during school improvement initiatives. Drawing from in-depth interviews with 22 teachers, the research investigates the impact of distributed leadership on teacher practices, school culture, and student learning outcomes. Five prominent themes emerge from the analysis: collaboration and shared decision-making, empowerment and teacher agency, challenges within distributed leadership, the transformative impact on teaching and student learning, and the professional growth and development of educators. These themes underscore the profound influence of distributed leadership on teachers' roles, autonomy, and contribution to school improvement. These themes reflect the nuanced experiences of teachers, highlighting the positive influence of distributed leadership on their professional growth, teaching practices, and student outcomes. The study's findings underscore the transformative potential of distributed leadership in fostering collaboration and shared decision-making, empowering teachers, and contributing to school improvement. The implications drawn from this research offer valuable guidance for educational institutions seeking to enhance leadership models, inspire teacher leadership, and drive continuous improvement in the education sector. As educational organizations seek to optimize leadership models, the insights gleaned from this study offer a roadmap for enhancing teaching practices, student outcomes, and the holistic betterment of educational institutions.